2005
DOI: 10.1109/tcomm.2005.857165
|View full text |Cite
|
Sign up to set email alerts
|

Turbo Codes With Rate-<tex>$m/(m+ 1)$</tex>Constituent Convolutional Codes

Abstract: The original turbo codes (TCs), presented in 1993 by Berrou et al., consist of the parallel concatenation of two rate-1/2 binary recursive systematic convolutional (RSC) codes. This paper explains how replacing rate-1/2 binary component codes by rate-(+ 1) binary RSC codes can lead to better global performance. The encoding scheme can be designed so that decoding can be achieved closer to the theoretical limit, while showing better performance in the region of low error rates. These results are illustrated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
88
0
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(96 citation statements)
references
References 19 publications
1
88
0
4
Order By: Relevance
“…초기의 DVB-RCS 표준안으로 채택되어진 이중이 진 Turbo 부호의 성능이 오류 마루(error floor) 현상 이 발생하여 [1] , 이를 개선하기 위해 새로운 알고리즘 들이 DVB-RCS NG(Next Generation)에서 제시되고 있다 [2], [3] . 새롭게 제시되고 있는 부호화 방식으로는 비선형 위성 채널에서 효율적인 CPM(Continuous Phase Modulation) 기반의 연판정 e-BCH(extended-BCH) 부호가 효과적임이 입증되었다.…”
Section: ⅰ 서 론unclassified
“…초기의 DVB-RCS 표준안으로 채택되어진 이중이 진 Turbo 부호의 성능이 오류 마루(error floor) 현상 이 발생하여 [1] , 이를 개선하기 위해 새로운 알고리즘 들이 DVB-RCS NG(Next Generation)에서 제시되고 있다 [2], [3] . 새롭게 제시되고 있는 부호화 방식으로는 비선형 위성 채널에서 효율적인 CPM(Continuous Phase Modulation) 기반의 연판정 e-BCH(extended-BCH) 부호가 효과적임이 입증되었다.…”
Section: ⅰ 서 론unclassified
“…A code matched symbol interleaver of length symbols is used. A symbol interleaver allows symbol probabilities to be exchanged during the iterative process, which gives improved convergence [11]. The design of the symbol interleaver has to take into account Turbo code crossed error events similar to the (information weight ) example shown in Fig.…”
Section: Encodermentioning
confidence: 99%
“…This corresponds to a decoder treating user B as interference. It can be shown that (9) becomes 1 (11) This can be split into two separate decoders with (12) where is a multiplicative constant, and . In (12) the MAP summation is performed over the state space of only one user.…”
Section: Decodermentioning
confidence: 99%
“…Recently, nonbinary turbo codes have received a great deal of attention and are adopted in several mobile radio systems such as DVB-RCS and IEEE 802.16 standard (WiMAX) [2], as they can offer many advantages over single-binary turbo codes [3].…”
Section: Introductionmentioning
confidence: 99%